The Influence of Different Language Instruction on the Self-Perception of the Students in Azerbaijan - Huseynzada, Garib (ADA University, 2022)
A growing number of the enrollment in the classes where the main language of instruction is Russian has caused tension in society. An ongoing debate in Azerbaijani society revolving around whether Russian-medium is a threat to instilling national values in the students. This study explored the value differences between the students studying in Azerbaijani- and Russian-mediums. The design of the study aligns with quantitative research. A questionnaire as a survey instrument was sent to the participants who study in Azerbaijani- and Russian-mediums in order to collect the data. Cronbach’s Alpha of the instrument constituted 0.978 implying high reliability. In order to analyze the data and reveal the statistically significant differences between groups, the Mann-Whitney U test was used. The participants studying in Azerbaijani-medium significantly rated themselves higher on the items related to Physical Ability, Self-Regulation, Peace, Co-Operation, Caring, Feeling Valued, etc. On the other hand, the participants studying in Russian medium scored higher on the items related to Appearance, Reading, Creativity, and Self Management. Also, both gender- and age-specific differences appeared in each medium. For policymakers, raising awareness about the influence of the schooling of Azerbaijan on Russian-medium students is recommended to promote social cohesion in society.
Keywords: Language instructions.; Language instructions -- Russian language.; Education, Higher -- Azerbaijan.; Education